Evaluasi Efektivitas Program Penanggulangan Kebakaran oleh Satuan Polisi Pamong Praja dan Pemadam Kebakaran Kabupaten Ngawi dalam Meningkatkan Perlindungan Masyarakat - Sultan Setiawan; Ika Devy Pramudiana; Sapto Pramono; Sri Roekminiati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Fire is one of the serious threats that can disrupt the security, safety, and survival of the community, especially in areas with limited disaster management systems. Ngawi Regency as a developing area requires an effective fire management system to provide maximum protection to the community. This study aims to evaluate the effectiveness of the fire management program implemented by the Civil Service Police Unit and the Ngawi Regency Fire Department in improving community protection. This study uses a qualitative approach with a descriptive study type. Data were collected through in-depth interviews, participatory observation, and documentation. All data obtained were analyzed using the Miles and Huberman interactive analysis model, through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the program is not yet fully effective, characterized by planning that is less based on risk data, uneven implementation across regions, and low socialization and community participation. The conclusion of this study states that the success of the program is highly dependent on adaptive planning, equitable distribution of resources, and active community involvement. For further research, it is recommended to develop an integrated quantitative and qualitative indicator-based evaluation model, as well as a comparative study between regions to obtain a broader picture of best practices in fire management at the regional level.